Corneal confocal microscopy differentiates patients with secondary parkinsonism from idiopathic Parkinson’s disease - Hong-Qi Yang; Ran Xin; Ning-Ning Che; Qiu-Huan Jiang; Shuai Chen; Si-Yuan Chen; Zhi-Kun Sun; Wei-Min Yang; Xue Li; Jian-Jun Ma; Jie-Wen Zhang; Rayaz A. Malik (npj Parkinson's Disease)
Abstract Parkinson’s disease (PD) is characterized by progressive degeneration of dopaminergic neurons in the substantia nigra, while secondary parkinsonism (SP) may be due to drugs, vascular, infectious, inflammatory, or even paraneoplastic etiologies. There is currently no biomarker that accurately distinguishes SP from PD. Corneal confocal microscopy (CCM) identifies corneal nerve loss which is associated with motor, cognitive and autonomic dysfunction in PD patients. This study enrolled participants with PD (n = 45) and SP (n = 25). A subset of patients underwent L-6-18F-fluoro-3,4-dihydroxyphenylalanine (18F-DOPA) positron emission tomography (PET) scan which showed bilateral decreased dopamine uptake in the putamen and caudate of patients with PD, but not in those with SP. Corneal nerve fiber density (CNFD) (P < 0.001) was lower and corneal nerve branch density (CNBD) (P = 0.007) was higher in the PD group compared to the SP group. The receiver operating characteristic (ROC) analysis revealed that combined CNFD and CNBD showed excellent discrimination between SP and PD, with an area under the curve (AUC) of 0.924. CCM may have clinical utility in differentiating patients with SP from PD.